Hsp90: breaking the symmetry - Mayer, Matthias P.; Le Breton, Laura (Molecular cell, 2015)
Hsp90 chaperones receive much attention due to their role in cancer and other pathological conditions, and a tremendous effort of many laboratories has contributed in the past decades to considerable progress in the understanding of their functions. Hsp90 chaperones exist as dimers and, with the help of cochaperones, promote the folding of numerous client proteins. Although the original view of these interactions suggested that these dimeric complexes were symmetrical, it is now clear that many features are asymmetrical. In this review we discuss several recent advances that highlight how asymmetric interactions with cochaperones as well as asymmetric posttranslational modifications provide mechanisms to regulate client interactions and the progression through Hsp90’s chaperone cycle.
Gesehen am 10.06.2020